Prolific domains : on the anti-locality of movement dependencies - Grohmann, Kleanthes K. (Linguistik aktuell, 2003)
Standard conceptions of Locality aim to establish that a dependency between two positions may not span too long a distance. This book explores the opposite conception, Anti-Locality: Don't move too close. The model of clause structure, syntactic computation, and locality concerns Kleanthes Grohmann develops makes crucial use of derivational sub-domains, Prolific Domains, each encapsulating particular context information (thematic, agreement, discourse). The Anti-Locality Hypothesis is the attempt to exclude anti-local movement from the grammar by banning movement within a Prolific Domain, a Ba.